A novel size-dependent quasi-3D isogeometric beam model for two-directional FG microbeams analysis. (1st March 2019) - Yu, Tiantang; Zhang, Jiankang; Hu, Huifeng; Bui, Tinh Quoc
Abstract: A two-directional functionally graded microbeam model is developed for natural frequency and mechanical bending analysis by using NURBS–based isogeometric analysis combined with a non-classical quasi-3D beam theory (NCQ3BT). Material parameters of microbeam continuously and smoothly change along thickness and axial directions. The small size effects are seized with the modified couple stress theory. In the NCQ3BT, both normal and shear deformations are considered without the need for the shear correction factor. The high-order continuity of NURBS directly meets the demand of C 1 -continuity in the NCQ3BT. Numerical results prove the superior performance and accuracy of the developed approach. The influences of material gradient factors along the axial and thickness directions, material length scale factor, boundary condition, and other aspect ratios of two-directional FG microbeams on mechanical behavior are investigated.